Micromorphology of paleosols at the continental border of the Buenos Aires province, Argentina - Cumba, Andrea (2004)
The sediments with loessial characteristics of the Pampean plain are called “loess y limos pampeanos” (Pampean loess and silts), to distinguish those of purely eolian origin (loess) from those reworked by water (silts). In the continental border of La Plata River, mainly loess-like sediments of the late and middle Pleistocene outcrop, approximately at 20 km from the shoreline. Between that border and the shoreline they underlie at 2–5 m depth the Holocene sediments deposited by the regressive events in a successive lowering of sea level during the late 6,000 years. The objectives of this work are: a) to integrate previous and new information on several sedimentary successions, b) to study the micromorphological features of the paleosols and c) to carry out a regional correlation of paleosols between the localities of San Pedro and La Plata based on field and micromorphological features. The profiles are between 18.5 and 12.5 m a.s.l. with macroscopic pedological features which show partially continuous development. The buried paleosols are superposed and welded, with different degrees of pedogenesis indicated by macro- and micromorphological features of illuviation and hydromorphism. In some cases, these features would have formed simultaneously with the deposition of the eolian dust trapped by grass. The degree of pedogenesis would depend on the ratio between the intensity of the accretion and reworking processes, and pedogenesis. The sedimentary units were affected partially or totally by pedogenesis. Two zones rich in volcanic glass were detected at San Pedro profile; new information reveals the same situation near La Plata city. The uppermost zone, with 20–30% volcanic glass, constitutes in some cases the parent material of the present soil; the deeper zone, contains 50–70% volcanic glass. Micromorphological observations confirm the presence of scarce to abundant clasts of old illuvial horizons and loess embedded in the matrix of most of the paleosols. Pedological processes are most evident in the deeper part of the profiles, indicated by a strong grade of structure and abundant laminated and juxtaposed textural and amorphous features. The lower paleosols can be considered pedostratigraphic units useful for correlation in the continental border in northeastern Buenos Aires Province, Argentina.